A primary germ cell tumour in the gastrointestinal tract: a caecal lesion of yolk-sac morphology in a young patient. Issue 11 (1st November 2018) - Vishnoi, V; Liebenberg, P; Reid, F; Ward, A; Draganic, B
Abstract: A 24-year-old man with a history of Crohns disease, whilst undergoing surveillance colonoscopy was found to have an ulcerated caecal lesion. The histopathology from the mucosal biopsy was suggestive of a yolk sac tumour. After thorough re-examination, the patient had no radiological evidence of malignancy in his testes or retroperitoneum. His alpha-fetoprotein levels returned as 2145, whilst his carcinoembryonic antigen was negligible. The patient was therefore consented for and underwent a laparoscopic right hemi-colectomy with an ileocolic anastomosis, without any complications. The formal histopathology confirmed the results from the biopsy, of a yolk sac non seminous germ cell tumour with positive lymph nodes and lymphovascular invasion. The patient was referred on to medical oncology for neoadjuvant chemotherapy. As the literature in his instance is scarce, the patient's overall prognosis remains unclear. To the best of our knowledge this is the first reported primary germ cell tumour of the gastrointestinal tract.